Comparison of multi code link-layer transmission strategies in 3Gwireless CDMA. - Fitzek, F.H.P.
Within this article we investigate the possibility of using multiple codes within a code-division multiple access system to reduce the losses in a delay bounded transmission for 3G multimedia applications over wireless links with fading. Multiple codes are used to recover from gaps on the wireless link after a fading period by means of ARQ-type retransmissions. One key feature of our work is that even a small number of multiple codes leads to a dramatic reduction of losses regarding delay bounds of multimedia applications
Keywords: 3G multimedia applications; 3G wireless CDMA; ARQ-type retransmissions; Code-division multiple access; Delay bounded transmission; Fading; Losses; Multi code link-layer transmission strategies